HYGROPHILOUS HERBACEOUS V EGETATION OF CATALONIA. RETRIEVAL FROM THE DATA BANK FLORACAT - NINOT, J.M.; CARRILLO, E.; FONT, X. (Annali di Botanica, 1999)
From the data gathered in FloraCat, a synthesis of the herbaceous hygrophilous communities of Catalonia is presented, under the form of a phytocoenological sheme. 100 associations have been considered, as clearly documented through relevés from the area. For each one, the biogeographic character, the frequency or rarity in the area and the level of knowledge is expressed in the same scheme. Most of the associations are rare or very rare in general, and mainly those of Mediterranean character, which represent in most cases tiny spots of particular vegetation within xerophilous landscapes. As for phytocoenological knowledge, Boreo-Alpine communities are more or less well known, whereas data on Mediterranean associations are much more sparse, a half of them being poorly to very poorly known.